Emergency Management For Palate Fractures Accompanied By Dentoalveolar Fractures In Maxillofacial Trauma Patients - Syarifah Nova Amiza Zam; Fuad Fatkhurrohman; Noor Dyah Permatasari; Rasyida Reika Dewinta; Izzaz Zayyan Listy Putri; Fidela Matta Nydia; Isnaini Lailatul Adha Mujiningtyas (SONDE (Sound of Dentistry), 2024)
Introduction: Maxillofacial trauma is an injury related to the face or jaw caused by physical force, foreign objects, or burns, including injury to any of the bone structures, skin, and soft tissue of the face. Every part of the face may be affected, the eyes and their muscles, nerves and blood vessels may be injured which can cause visual disturbances, diplopia, dislocation of the eyeball and the orbital bones can be fractured due to being hit by something strong. Case report: Initial examination carried out pain screening using the Numeric Rating Scale (NRS) method showing a score of 4. Assessment of the level of consciousness using the Glasgow Coma Scale (GCS) method showed a GCS result of 15 (E4 M6 V5). Vital signs examination showed blood pressure 134/78 mmHg, pulse 112x/minute, height 160 cm, weight 90 kg, respiration 22x/minute, temperature 36.4 C, oxygen saturation 98%. Physical examination of the patient found that the head was within normal limits, the lip mucosa was wet (+). In the oral and nasal cavities, sources of bleeding and loose teeth are visible. On eye examination, the skin was normal. Thorax examination was normal. The management carried out was administration of intravenous fluids (inf RL 20 tpm), then injection of 1 ampoule of ranitidine, 1 ampoule of ketorolac injection, 500 mg tranexamic acid injection. The patient was also referred to a dentist who specializes in oral surgery for further examination and treatment. Conclusion: The classification of the dentoalveolar fracture in this patient is based on the Ellis and Davey classification, as a class 7 fracture, namely a fracture of the tooth that causes a change in position or displacement of the tooth. This fracture causes loose teeth and injury to the gingival soft tissue. The ideal dentoalveolar fracture treatment in this patient uses interdental wiring so that the teeth can be maintained properly. The patient was also referred to a dentist who specializes in oral surgery for further examination and treatment.